Effectiveness of computer education management in selected public secondary schools in the Division of City Schools Quezon City - Yangco, Gilbert B. 1951- (2008)
This study predicts computer education program effectiveness of schools in the Division of City Schools in Quezon City to provide guidelines to school administrators and teachers for an improved program implementation. Data were obtained through survey questionnaires for principals, computer education teachers, and students, with a follow up interview for the principals and assessment of student performance using the Computer Education Achievement Test, grade in computer education, and participation in computer skills contests. It was concluded that better school computer facilities, leading skills of principals, and a smaller school population contribute to higher academic achievement of students in computer education and increase chances of winning computer contests. School computer facilities singly affects student performance.